SELF-LOVE, SELF-CARE: INVESTIGATING THE RELATIONSHIP BETWEEN SELF-COMPASSION, SELF-AFFIRMATION, AND MENTAL HEALTH IN NURSING STUDENTS - Nakamura, Hiroshi (Research Journal of Health, Medicine and Nursing, 2024)
In Japan, despite the full university enrollment era, there has been a significant increase in the number of universities and nursing schools. This expansion aligns with the rising demand for nurses, amplified by factors like the impact of new coronavirus infections. As of recent records, there are approximately 1.27 million nurses in Japan, as reported by the Japan Nurses Association. However, this increase in numbers does not eliminate the persisting issue of high turnover rates in the nursing profession. One contributing factor is nurses' tendency to internalize others' distress, which often leads to empathy fatigue, secondary stress, and self-negative cognitions. These emotional burdens can culminate in burnout. This paper emphasizes the importance of self-compassion as a crucial factor in addressing burnout, particularly in scenarios where nurses consistently grapple with empathy fatigue and secondary stress. By examining the dynamics of selfcompassion, this study seeks to provide valuable insights into strategies for alleviating the burnout crisis among nurses in Japan